Age-Related Antimicrobial Resistance in Adults with Lower Respiratory Tract Infections in Nepal (Nepal Journal of Health Sciences, 2025)
Introduction: Lower respiratory tract infections remain a major health burden in Nepal, and the rising prevalence of antimicrobial resistance poses a significant challenge, particularly in older adults.Objectives: To evaluate antimicrobial resistance patterns among adults with lower respiratory tract infections in Nepal, with a focus on age-related differences.Methods: This retrospective analysis looked at 1,636 culture-positive respiratory specimens collected at Dhulikhel Hospital between January and December 2024. The Clinical and Laboratory Standards Institute guidelines were followed. Extended-spectrum beta-lactamase production was confirmed phenotypically, and multidrug resistance was defined as non-susceptibility to at least one drug in three or more antimicrobial classes. The relationship between age (≥60 years) and resistance outcomes was determined using multivariable logistic regression.Results: Klebsiella pneumoniae (24.90%), Streptococcus pneumoniae (17.50%), and Pseudomonas aeruginosa (11.80%) were the most common isolates. Compared to younger adults, elderly patients (≥60 years) showed a significantly higher prevalence of Multidrug Resistance (56.10% vs 47.20%, p = 0.004) and a higher prevalence of Extended-spectrum beta-lactamase production (31.60% vs 24.50%, p = 0.01). Elderly age was validated by multivariable analysis as an independent predictor of both Extended-spectrum beta-lactamase production (aOR 1.42, 95% CI 1.03–1.97) and Multidrug Resistance (aOR 1.36, 95% CI 1.07–1.74). There were no appreciable age-related differences in the 11.4% of isolates with carbapenem resistance.Conclusion: Adult lower respiratory tract infection patients in Nepal show high antimicrobial resistance rates, with multidrug resistance and Extended-spectrum beta-lactamase pathogens mainly affecting older adults, emphasizing the need for better infection control, age-specific treatments, and antimicrobial stewardship.